Experimental investigation of kerf of Ti6Al4V exposed to different heat treatment processes in WEDM and optimization of parameters using genetic algorithm - Altug, Mehmet; Erdem, Mehmet; Ozay, Cetin (Springer London Ltd, 2015)
In this study, microstructure, mechanical, and conductivity characteristics of alloy Ti6Al4V were changed with different heat treatments and the effect of such characteristics on its machinability with wire electrical discharge machining (WEDM). Optical microscope, scanning electron microscope (SEM), and X-ray diffraction (XRD) examinations were performed to determine various characteristics, and additionally microhardness and conductivity measurements were conducted hereof. L18 Taguchi test design was conducted with three levels and six different parameters to determine the effect of such alterations on its machinability with WEDM, and post-processing kerf (cutting width) values were determined. Microchanges were ensured successfully by using applied heat treatments. Results obtained with the optimization technique of genetic algorithm gave minimum kerf. Values obtained by using response surface method along with this equation completely match with those achieved in the experiments. The best kerf value was obtained from sample E which was quenched from dual phase area. The microstructure of this sample was composed of primary alpha and alpha' phases.
Keywords: Ti6Al4V; Heat treatment; Microstructure; WEDM; Kerf; Genetic algorithm